7-(3n-8)=-6

Simple and best practice solution for 7-(3n-8)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(3n-8)=-6 equation:


Simplifying
7 + -1(3n + -8) = -6

Reorder the terms:
7 + -1(-8 + 3n) = -6
7 + (-8 * -1 + 3n * -1) = -6
7 + (8 + -3n) = -6

Combine like terms: 7 + 8 = 15
15 + -3n = -6

Solving
15 + -3n = -6

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + -3n = -6 + -15

Combine like terms: 15 + -15 = 0
0 + -3n = -6 + -15
-3n = -6 + -15

Combine like terms: -6 + -15 = -21
-3n = -21

Divide each side by '-3'.
n = 7

Simplifying
n = 7

See similar equations:

| 7x^2+3=5 | | -10+9x=12 | | -x+6y=-1 | | 6-(2)(3)= | | 0.4(2x-0.5)=3[0.2x-(-2)]-4 | | 9x^2-3x-45=0 | | -3(5x+3)=-144 | | 1=3b | | 18-12n=16+3n-11 | | 4m=256 | | simplify5/13(75-49) | | 3(4x+5)=-5+53 | | 4m=156 | | 12+6x-3x=30 | | (x+1)[2(3x-1)-(4+5x)]=2(x-1)(x+2)+4 | | 0.2=-1.2n-7 | | Y=-2(-6)+4 | | -8(z-9)=3-7z | | -9(-6v+y-3)= | | Log(2)(x)=3 | | 12+6x-3x= | | 3(a+2)-8=5-2(a+4) | | x/3-x/10=7 | | y-2=-2/7(x-3) | | 4y+9(-0.4444444444y)=0 | | y=-4(4)+2 | | 3(x+4)+5x=76 | | 13-2n=9 | | -9-6x=x-3 | | 167/8=3/10 | | f(t)=(0.12)t | | 5(3x-1)=-2(x-6) |

Equations solver categories